EVALUASI LANSKAP SITU-FRONT SEBAGAI PENGEMBANGAN WATERFRONT DI KAWASAN CIBINONG RAYA, KABUPATEN BOGOR - Intan Dewi Puspita; Indung Sitti Fatimah; Andi Gunawan (http://arl.faperta.ipb.ac.id/, 2017)
Water resources is a natural element that has an important role in the development of a city. Not only on the land, development of the city can be done up to the water's edge. Among the aquatic and urban development zone of interaction it is called waterfront. the principle on planning a waterfront region is to build a public open space in urban areas that are physically and visually facing to the water (beach/river/lake) and can be a forum for community activities. To establish the identity and character of the city, Cibinong Raya was designed with Situ-front City because the city has 17 lakes on its territory. Those lakes in Cibinong Raya has different size and physical condition distinct from one another that could affect the priorities in its development. The study was conducted to evaluate the area around lakes in Cibinong Raya in accordance with waterfront development concept. Assessment on the condition of lakes in Cibinong Raya applies the criteria waterfront, riparian ecosystem status criteria, and the criteria for the status of aquatic ecosystems. The results showed that there are 3 lakes is in good condition and 4 lakes in passably condition to be developed into waterfront area.